Análisis de los compuestos fenólicos antioxidantes en diferentes bagazos de cerveza artesanal “Master Beer” (2022)
The brewing process generates a large amount of waste that could be reused. Beer bagasse is the most abundant by-product of the brewing industry, representing 85% of the total waste generated. The large volume of this material, its low cost and its components make it a high potential resource for recycling or utilization. The objective of this work is to analyze three different malts from the Master Beer company (Wheat, Munich and Pilsen) in Bogota, where a previous conditioning, drying and milling process was carried out. Natural antioxidants were extracted by means of soxhlet-type solid-liquid extraction with three different concentrations of ethanol (80%, 60% and 40%). Once the extractions were finished, distillation was carried out to eliminate the solvent and the total polyphenol content was measured by the Folin-Ciocalteau method and the antioxidant capacity by DPPH analysis. Wheat malt with the 60% ethanol concentration showed that, with this treatment, the best results in phenol content (7.87 mg GAE/ g BSG) and antioxidant activity (85%) were obtained. In conclusion, beer bagasse can be an important source of natural antioxidants. Obtaining its extract is feasible and provides added value to what is currently only an organic waste.